TEXCT COMPLEXITY: THE STORK HAS ARRIVED (STORY) BY SAID AHMAD - Erkinova Muqaddas Olim qizi; Jo‘rayev Muhammadrahimxon Murod o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Text complexity represents a multifaceted construct that encompasses linguistic, cognitive, and structural dimensions influencing how readers process and comprehend written discourse. Contemporary research conceptualizes text complexity through quantitative indices—such as lexical sophistication, syntactic density, and readability formulas—and qualitative attributes including coherence, cohesion, discourse structure, and conceptual load. Scholars argue that evaluating text complexity requires an integrative framework that captures both surface-level features (word frequency, sentence length, morphological variation) and deep-level elements (semantic depth, inferential demands, and genre conventions). Advances in computational linguistics and natural language processing have significantly expanded the precision of complexity measurement, enabling automated assessments across diverse textual corpora. These analytical tools contribute to curriculum design, literacy development, and appropriate text–reader alignment in educational contexts. Ultimately, understanding text complexity is essential for optimizing reading materials, supporting differentiated instruction, and enhancing comprehension outcomes across various proficiency levels.